Analisis Strategi Dalam Penyelesaian Kredit Bermasalah pada PT. BPR Aswaja Ponorogo - Nanda Sari, Puput; Mustoffa, Ardyan Firdausi (Universitas Muhammadiyah Ponorogo, 2023)
â€This study aims to determine the implementation of existing strategies in PT. BPRÂ AswajaÂ PonorogoÂ for the 2018-2020Â period. The method applied in this research is a qualitative method which is carried out using interview techniques and documentation techniques. The results of the study indicate that the factors that influence non-performing loans are the debtor himself and the debtor's awareness to fulfill his obligations, as well as the global economic situation. Banks' efforts in rescuing non-performing loans are restructuring, namely saving credit by adding arrears of principal or interest to the principal loan, reconditioning saving non-performing loans by reducing interest rates, reschedulingÂ rescheduling, or extending the installment payment period, as well as liquidation by selling.Â againstÂ the collateral used as collateral if the customer has not paid off the dependents. Keywords: Non-performing Loans, Non-performing Loans Resolution Strategy,Â Restructuringâ€.